ALIH KODE DAN CAMPUR KODE DALAM FILM MOHON DOA RESTU: KAJIAN SOSIOLINGUISTIK - Dewi, Nisrina; Imas Juidah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to describe the phenomena of code-switching and code-mixing as representations of traditional and modern identities in the film Mohon Doa Restu by Ody C. Harahap. The linguistic dynamics in this film reflect the clash of cross-generational values between parents and children. The method used is qualitative descriptive with a sociolinguistic approach. The research data consists of lingual units containing elements of code-switching and code-mixing, collected through the observation and note-taking method. The results reveal 24 data of speech events, comprising 15 instances of code-mixing and 9 instances of code-switching. Code-mixing is dominated by the insertion of English and Sundanese into an Indonesian base. The findings reveal that code-switching into Sundanese by the older generation characters serves to reinforce traditional authority, whereas the use of English by the younger generation represents an urban-global identity and professional independence. This study concludes that the use of language codes is not merely a speech variation but an identity negotiation strategy in facing value conflicts within a multilingual society.